2010
DOI: 10.3109/09537101003660564
|View full text |Cite
|
Sign up to set email alerts
|

Annexin V binding to platelets is agonist, time and temperature dependent

Abstract: Platelets bind annexin V when stimulated with combinations of platelet agonists such as collagen and thrombin. Previous studies have demonstrated significant heterogeneity of platelets binding annexin V. The relative role of the thrombin protease-activated receptors (PARs) PAR1 and PAR4 together with different methods of platelet preparation on annexin V binding to platelets is unclear. We therefore investigated the role of PAR1-and PAR4-activating peptides in combination with collagen-related peptide on annex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 25 publications
5
15
0
Order By: Relevance
“…In agreement with the previous reports (Dale et al , 2002; Keuren et al , 2005; Ramstrom et al , 2010), there are three possible ways to initiate platelet activation so that two subpopulations with different PS expression will be ultimately produced: via either GPVI, PAR1, or PAR4. The sizes of the subpopulations can be additionally modulated by adenosine 5′disposphate acting via the P2Y12 receptor, while thromboxane A2 signalling and the P2Y1 receptor do not appear to contribute significantly (Kotova et al , 2008).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In agreement with the previous reports (Dale et al , 2002; Keuren et al , 2005; Ramstrom et al , 2010), there are three possible ways to initiate platelet activation so that two subpopulations with different PS expression will be ultimately produced: via either GPVI, PAR1, or PAR4. The sizes of the subpopulations can be additionally modulated by adenosine 5′disposphate acting via the P2Y12 receptor, while thromboxane A2 signalling and the P2Y1 receptor do not appear to contribute significantly (Kotova et al , 2008).…”
Section: Discussionsupporting
confidence: 90%
“…Comparative contribution of PAR1 and PAR4 to thrombin‐induced procoagulant activity has been a subject of some controversy. Different reports suggested either that PAR1 is predominant and determines the effects of thrombin (Andersen et al , 1999; Keuren et al , 2005; London et al , 2004), or that PAR1 has a minor role, if any (Dicker et al , 2001), or that PAR1 and PAR4 are comparable (Ramstrom et al , 2010), or that even stimulation of both receptors cannot explain the effects of thrombin (Dorsam et al , 2004). These studies differ by the platelet isolation method (unless performed directly in whole blood), the type and degree of platelet activation (with or without stimulation of collagen receptors), the methods of receptor stimulation/inhibition, and the methods of procoagulant activity characterization (PS detection or coagulation factor activation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Bevers et al in 1982 [5] clearly identified that collagen is more potent, but that the combination of collagen and thrombin greatly potentiated the capability of platelets to support thrombin formation [5]. The small percentage of phosphatidylserine (PS)-positive platelets reported in this paper are well in accordance with other studies [14,27,28], where only a small percentage of platelets turn PS positive even in response to high concentrations of thrombin, although it should be noticed that PS exposure determined by annexin V binding could vary considerably as a result of variations in experimental conditions [29]. The important contribution by collagen is also evident in this paper, as the combination of thrombin and collagenrelated peptide in Fig.…”
supporting
confidence: 91%
“…This causes integrin activation, granule secretion and an increase in intracellular Ca 2+ [18,19,21,22]. Activation of GPVI is also highly important for the exposure of procoagulant phosphatidylserine [23][24][25].…”
mentioning
confidence: 99%